2019
DOI: 10.3846/gac.2019.8555
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Approach to the Integral Assessment of the Regional Lands Use Territorial Development

Abstract: The relevance of the research topic is caused by the need to ensure the territorial development of land use at the regional level. In this context, it is necessary to form a quantitative basis for assessing territorial development, which will make decisions in the field of land use and ensure the growth of land use efficiency in the region, considering spatial, urban planning, ecological and investment areas. As a result of the study, a methodological approach to the integrated assessment of the territorial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
5
0
4
Order By: Relevance
“…At a low level, these processes took place in the Chernivtsi, Zaporizhzhia, and Zakarpattia regions. Spatial information on the use of land plots in their transfer to ownership is carried out according to the following characteristics: a cadastral number of the land plot; customer; developer; affiliation; type and features of formation and use of documentation; location; purpose; directions; and features of transformation (Mamonov, 2019a).…”
Section: Spatial Provision Of Information Regarding the Formation Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…At a low level, these processes took place in the Chernivtsi, Zaporizhzhia, and Zakarpattia regions. Spatial information on the use of land plots in their transfer to ownership is carried out according to the following characteristics: a cadastral number of the land plot; customer; developer; affiliation; type and features of formation and use of documentation; location; purpose; directions; and features of transformation (Mamonov, 2019a).…”
Section: Spatial Provision Of Information Regarding the Formation Of ...mentioning
confidence: 99%
“…However, the solution to problems related to the formation of a multi‐purpose cadaster through the prism of the application and improvement of land cadastral information is not enough (Enemark, 2005; Enselm, 2002; Karpinsky, 2004; Karpinsky, 2006; Lyashchenko, 2007; Lyashchenko, 2008; Osterom, 2006; Volodin, 2000). Therefore, it is proposed to determine the levels and features of stakeholder relations and areas of territorial development at the regional level (Mamonov, 2019a; Mamonov et al, 2018; Mamonov, Dymchenko, et al, 2021; Mamonov, Kondrashenko, et al, 2020; Mamonov, Sklyar, et al, 2021; Mamonov, Velychko, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Representatives of the system approach define geoecological monitoring of land use from the standpoint of forming and applying a complex of actions, modern tools based on quantitative assessment for the implementation of monitoring procedures, taking into account the peculiarities of land relations [12][13][14][15][16].…”
Section: Analysis Of Theoretical Provisionsmentioning
confidence: 99%
“…Thus, intelligent systems are defined as a modern complex set of tools based on the application of the artificial intelligence, with the implementation of technological means of developing expert, advisory, intelligent information search, logical calculation systems based on the information background and aimed at solving problems, defining algorithms, program systems that can replace a human being and create a basis for decision taking. The concept of the territorial development of land administration at the regional level is based on the theoretical and methodological provisions developed within the following studies: Yeroshkina (2009), Mamonov (2018aMamonov ( , 2018bMamonov ( , 2019aMamonov ( , 2020a, Kravtsiv (2015). The research showed discrepancies in the theoretical and methodological approaches to defining the territorial development of land administration in the regions and offered it major characteristic as a combination of spatial, urban planning, investment and environmental factors, the interrelation of which results in achieving a new stance of the land administration quality compared to the past, taking into account social, institutional, managerial peculiarities and the degree of the stakeholders' involvement in the area of the land administration in the regions (Mamonov, 2019b;Mamonov et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%